(untitled) (Al Fiddhoh: Journal of Banking, Insurance, and Finance, 2025)
Professional, transparent, and accountable zakat management is an urgent necessity to address public trust challenges toward zakat institutions. This makes the implementation of Good Amil Governance important to study, given its role in strengthening institutional legitimacy and the effectiveness of zakat distribution. This research aims to analyze the implementation of Good Amil Governance in zakat institutions in Indonesia and to examine accountability standards that support integrated governance. The research method employed is a literature study with a descriptive qualitative approach, reviewing regulations, previous studies, and governance practices in zakat management organizations. The findings indicate that the implementation of Good Amil Governance has shown significant progress, particularly in transparency, accountability, and professional management, although its consistency varies across institutions. The quality of amil human resources is proven to be a key factor in realizing good governance. Furthermore, zakat accountability standards encompass vertical dimensions (sharia compliance) and horizontal dimensions (public trust), supported by digital technology though not yet evenly applied. The implications highlight the importance of regulatory harmonization, integrated reporting systems, and strengthening amil capacity to enhance public trust, expand global philanthropic networks, and position zakat institutions as agents of social justice in sustainable development.